2020
DOI: 10.5435/jaaos-d-18-00254
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Obtaining Postmobilization Imaging in Nonsurgical Pelvic Ring Injuries

Abstract: Introduction: Pelvic fractures are diverse injuries with varying degrees of severity. Treatment recommendations are determined by the associated instability. For likely stable patterns, postmobilization imaging is used to assess for occult instability. This study assesses the utility of postmobilization images and determines how often they alter the recommendations for treatment. Methods: Records at a single level 1 trauma center from January 2007 throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 11 publications
2
19
0
Order By: Relevance
“…Similar to prior studies, we found that injuries with complete sacral fractures and bilateral rami fracturs have a higher risk of displacing greater than 10 mm than those with incomplete sacral fractures and unilateral rami fractures. 10,18 Combining our results with those of Winston et al 9 would suggest that widespread follow-up imaging on successfully mobilized LC1 pelvic ring injuries is not necessary outside of social or specific patient considerations in the inpatient or outpatient settings…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…Similar to prior studies, we found that injuries with complete sacral fractures and bilateral rami fracturs have a higher risk of displacing greater than 10 mm than those with incomplete sacral fractures and unilateral rami fractures. 10,18 Combining our results with those of Winston et al 9 would suggest that widespread follow-up imaging on successfully mobilized LC1 pelvic ring injuries is not necessary outside of social or specific patient considerations in the inpatient or outpatient settings…”
Section: Discussionsupporting
confidence: 65%
“…Similar to prior studies, we found that injuries with complete sacral fractures and bilateral rami fracturs have a higher risk of displacing greater than 10 mm than those with incomplete sacral fractures and unilateral rami fractures. 10,18 Combining our results with those of Winston et al 9 would suggest that widespread follow-up imaging on successfully mobilized LC1 pelvic ring injuries is not necessary outside of social or specific patient considerations in the inpatient or outpatient settings Because there is minimal risk of stable LC1 pelvic ring injuries displacing enough to necessitate operative intervention, obtaining multiple outpatient radiographs increases radiation exposure, raises health care costs, and does not add to patient care. The radiation from a single pelvis radiograph is estimated at 20 dGy per cm.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations